Fractal analysis of fracture systems in Upper Triassic Dolomites in Žumberak Mountain, Croatia (Rudarsko-geološko-naftni zbornik, 2017)
This paper presents results of fractal analysis of fracture systems in upper Triassic dolomites in Žumberak Mountain, Croatia. Mechanical rock characteristics together with structural and diagenetic processes results with fracture systems that can be considered as fractals. They are scale-invariant in specific range of scales. Distribution of fractures can be than described with power law distribution and fractal dimension. Fractal dimension is a measure of how fractures fill the space. Fractal dimension can be estimated form photographs of outcrops by converting photographs to binary photographs. In binary photo there is only black (rock or fractures) and white (fractures or rock). Fractal dimension is then estimated based on box-counting method. In this paper we present results of fractal analysis from three outcrops. Results are very similar to previous published results from outcrops of dolomites in Slovenia. Obtained fractal dimensions are in range 2,69-2,78 and it depends on how fracture systems are distributed in the outcrop. Lower values indicate smaller number of fractures and higher significance of larger fractures. Higher values indicate distribution of more similar sized fractures throughout whole outcrop. Fractal dimension is very significant parameter in rock fracture system characterisation sense it describes how fractures are distributed in the outcrop. It can be used in discrete fracture network modelling if spatial distribution of fractures is represented with power law distribution.